Effect of Umbilical Cord Cell Isolate Administration on STRO-1 and CD 34 Expression of Dental Pulp Stem Cell Culture - Nugraeni, Yuli; Rachmawati, Ranny; Az Zahra, Akyla Oktriza; Nugraha, Adelia Adzra (Journal of Biomedicine and Translational Research, 2025)
Background: Dental Pulp Stem Cell (DPSC) is one of the ideal mesenchymal stem cells (MSCs) for the repair of damaged cells, as it has great proliferative potential and the ability to regenerate pulp-like complex dentins. However, DPSC has limitations in providing stem cell sources due to its small number. Therefore, it is induced with umbilical cord cell isolate (hUC-MSC) which is currently widely developed because of its advantages that are easy to obtain, have proliferative potential, and have anti-inflammatory effects. However, its influence and effectiveness on Dental Pulp Stem Cells is not widely known.Objective: To prove the effect of umbilical cord cell isolate on the expression of Stro-1 and CD 34 in Dental Pulp Stem Cell (DPSC) culture.Methods: This study is experimental laboratory with simple random sampling which is divided into 4 groups, namely 2 control groups and 2 groups of umbilical cord isolate administration which are observed for 12 hours and 24 hours. Observation of expression by immunohistochemical staining was then calculated using Qupath software in 5 fields of view.Results: The treatment group that was given umbilical cord cell isolate showed the highest increase in Stro-1 and CD 34 expression at 24-hour observation compared to the untreated group.Conclusion: There was an increase in the expression of Stro-1 and CD 34 in Dental Pulp Stem Cell cultures after being given umbilical cord cell isolate.